2018
DOI: 10.3389/fpsyg.2018.01587
|View full text |Cite
|
Sign up to set email alerts
|

Affective Eye Contact: An Integrative Review

Abstract: In recent years, many studies have shown that perceiving other individuals’ direct gaze has robust effects on various attentional and cognitive processes. However, considerably less attention has been devoted to investigating the affective effects triggered by eye contact. This article reviews research concerning the effects of others’ gaze direction on observers’ affective responses. The review focuses on studies in which affective reactions have been investigated in well-controlled laboratory experiments, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
109
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 155 publications
6
109
0
3
Order By: Relevance
“…Overall, this study provides novel evidence confirming the relevance of eye contact in modulating human behaviour, at least under conditions that promote its contextual saliency, and aligns with the notion that eye contact is capable of amplifying different cognitive and physiological mechanisms [6][7][8][9][10] . In this regard, the fact that eye contact enhanced the reflexive component of overt gaze following fits nicely with the "fast track modulator" model pushed forward by Senju and collaborators 8,9 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Overall, this study provides novel evidence confirming the relevance of eye contact in modulating human behaviour, at least under conditions that promote its contextual saliency, and aligns with the notion that eye contact is capable of amplifying different cognitive and physiological mechanisms [6][7][8][9][10] . In this regard, the fact that eye contact enhanced the reflexive component of overt gaze following fits nicely with the "fast track modulator" model pushed forward by Senju and collaborators 8,9 .…”
Section: Discussionsupporting
confidence: 83%
“…Importantly, understanding whether another individual is looking at us is an essential ability to successfully navigate within social environments, since it may activate the execution of adequate approach-avoidance behavioural responses. Moreover, a bulk of studies has reported that establishing eye contact with others can also shape our physiological and cognitive responses profoundly, and different theoretical frameworks and models have been pushed forward to explain the impact of eye contact on human behaviour [6][7][8][9][10] . The overall picture emerging from this literature suggests that eye contact episodes are typically associated with incremental effects.…”
mentioning
confidence: 99%
“…Whereas perceived direct gaze from others is indicative of their communicative intent, observed averted gaze signals that the attention of others is directed elsewhere. Accordingly, perceiving the gaze of others has been shown to influence several socio-cognitive processes and behavioral responses in the observer (for relevant reviews, see Conty, George, & Hietanen, 2016;Hietanen, 2018;Senju & Johnson, 2009). In terms of mirror system activity, several TMS studies have shown that under various experimental conditions, perceived communicative intent from the actor (conveyed by different gaze cues) significantly modulates M1 excitability (MEP responses) in the observer (Betti et al, 2019;Prinsen & Alaerts, 2019;Prinsen et al, 2017;Prinsen, Brams, & Alaerts, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The perception of another individual's direct gaze is known to influence many aspects of human emotion, cognition, and behavior (for reviews, see Conty, George, & Hietanen, 2016;Hietanen, 2018;Kleinke, 1986;Senju & Johnson, 2009). Among other effects, another's direct gaze has been demonstrated to increase honest and prosocial behavior.…”
Section: Introductionmentioning
confidence: 99%